PENGARUH KOMPETENSI PROFESIONAL GURU IPA DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR IPA TERPADU PESERTA DIDIK KELAS IX SMP NEGERI 5 MIMIKA - Ngatinah, .; Rumahorbo, Basa T. (Magister Pendidikan IPA, UNCEN, 2014)
Influence Professional Competence and Motivation Learning Against Learning Achievement of Students in Integrated Science class IX in SMP Negeri 5 Mimika . The study was conducted using a questionnaire distributed to 54 students of grade IX with purposive sampling techniques and simple random addressing research sampling.Hasil no significant influence between science teacher professional competence variables ( X1 ) on learning achievement Integrated Science ( Y ) with r = 0.244 . Also there was no significant effect between learning motivation variable ( X2 ) on learning achievement Integrated Science ( Y ) with R = 0.178 . While jointly science teacher professional competence variables ( X1 ) and the variable learning motivation ( X2 ) on learning achievement Integrated Science ( Y ) with r = 0.185 . This means that there is no significant effect or effects are relatively small between science teacher professional competence , motivation toward achievement of learners Integrated Science class IX SMP Negeri 5 Mimika . Keywords: Professional Competence of Teachers, Motivation to Learn, Academic achievement, and Integrated Science